Comparison of Synovialization and Clinical Outcomes between Anterior Cruciate Ligament Anteromedial Bundle Augmentation and Double-Bundle Anterior Cruciate Ligament Reconstruction - Ahn, Gil Yeong; Hwang, Sung Hyun; Kang, Seo Won; Song, Jun Hyeok; Park, Jee Soo; Lee, Yeong Hyeon (The Journal of Knee Surgery, 2025)
This study aimed to compare clinical outcomes and second-look arthroscopic findings between double-bundle anterior cruciate ligament (ACL) reconstruction for complete ACL rupture and anteromedial (AM) bundle augmentation with preservation of the posterolateral (PL) bundle in isolated AM bundle rupture. Between 2014 and 2021, we retrospectively analyzed 95 ACL reconstructions with at least 2 years of follow-up. Patients undergoing primary ACL reconstruction from January 2014 to June 2021 were included in the study. Double-bundle ACL reconstruction (group 1) was performed in the cases involving male patients, high activity levels, age below 40 years, or when there was a patient preference for double-bundle reconstruction. In contrast, for partial ACL ruptures with an intact PL bundle confirmed on preoperative magnetic resonance imaging, AM augmentation was performed (group 2). Preoperative and final follow-up clinical outcomes, along with synovial coverage during second-look arthroscopy, were compared between group 1 (65 cases) and group 2 (30 cases). Statistical analysis included correlation coefficients between the groups. The Lysholm score, Tegner activity scores, and International Knee Documentation Committee (IKDC) knee evaluation form score at final follow-up were 81.8 (±5.5), 7.2 (±0.9), and 79.4 (±6.7), respectively, in group 1, and they were 88.0 (±6.4, p = 0.038), 7.9 (±0.5, p = 0.042), and 86.2 (±5.4, p = 0.081), respectively, in group 2. For group 1, the Lachman test (p = 0.093) and the pivot shift test (p = 0.176) at the final follow-up showed no laxity in 57 and 59 knees, and there was plus one laxity in 8 and 6 knees. For group 2, there were no laxity in 27 and 28 knees, and plus one laxity in 3 and 2 knees. Synovial coverage area percentages of the grafted tendon were 74.3 (±10.7) and 86.9 (±7.3, p = 0.002) in groups and group 2, respectively, with superior synovial coverage observed in group 2. The AM bundle augmentation with preservation of the PL bundle in ACL injury yielded better synovial coverage and clinical scores compared with double-bundle ACL reconstruction for complete ACL rupture.
Keywords: arthroscopic surgery; anterior cruciate ligament; anterior cruciate; ligament reconstruction